NEW APPROACHES TO REHABILITATION AMONG CHILDREN FROM HIGH RISK GROUPS OF TUBERCULOSIS - V.A. Aksenova; Yu.L. Mizernitsky; O.Yu. Senchikhina (Педиатрическая фармакология)
The research studied the impact of the mixture of bacteria lysates (IRS 19) on the recurrence of the acute respiratory infections among the weakened and sickly children from TB high risk group, who underwent rehabilitation at the anti TB health center. The researcher studied the tolerance to the physical loads (Shalkov test), secretory Iga concentration in the saliva, recurrence of the acute respiratory infections under supervision in catamnesis within a year. To prevent and treat bacterial nasal and respiratory infections, the authors used the mixture of bacteria lysates (Solvay pharma) along the specific chemical tuberculosis prevention. Performed complex rehabilitation increased the resistance of the children's body infected with TB mycobacteria and conduced to the increase of the normergic reactions to tuber culine. They revealed that the recurrence of the acute respiratory infections among the children, who received the mixture of bacteria lysates, made up 0,9 ± 0,2 among the children infected and 1,1 ± 0,2 non=infected with tb mycobacteria within the first 6 months of observation. In the test group, these indices came to 2,2 ± 0,3 and 2,3 ± 0,2, respectively. After they carried on the immunocorrection course, the saliva witnessed the increase of the secretory Iga concentration (among the children both infected and non infected with TB mycobacteria). performed research proves that it is clinically efficient, safe and expedient to introduce the seasonal course of the local immuno corrector — the mixture of bacteria lysates to the set of the rehabilitation actions among the children from TB high risk groups, which allows them to recommend wider application of this medication in children.Key words: mixture of bacteria lysates, tuberculosis, prevention, children.